Actions of the European Union and India for the development of Indian cities: cooperation between non-state and local actors - Pęczak, Maciej (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
The European Union actively participates in international initiatives for the sustainable development of urban areas. This is also the case with cooperation with India, which struggles with numerous urban problems such as environmental protection, lack of developed infrastructure, and urban economic management. The aim of this chapter is to present EU-India cooperation for urban development in India. It illustrates the impact of international agreements on the EU's urban policy developed over the years, joint EU-India initiatives, as well as selected examples of actions that have contributed to the real development of Indian cities. This allows for answering questions regarding the principles of EU urban policy, EU-India cooperation for the development of urban areas, and its effects.